Tenth Five-Year Plan Tamil Nadu 2002-2007 An Outline - Planning Commission (Planning Commission, 2002)
The Millennium’s First Five Year Development Plan for Tamil Nadu and the tenth since ushering in of planning era in the country has been formulated at a time when the economy of the nation is passing through a difficult phase with recession in the manufacturing sector and deceleration in growth. The deterioration in the finances of the States during the Nineties due to steep rise in revenue expenditures without a corresponding increase in revenue receipts, has reached alarming proportions threatening the very sustainability of the development process. Tamil Nadu has also gone through this process in the last few years. One of the key objectives of the Tenth Plan will, therefore, be to restore the fiscal balance and revive the State's economy.
State Planning Commission, Tamil Nadu